A Defence of the Resemblance Meaning of 'What it's like'. Issue 511 (31st October 2017) - Gaskin, Richard
Abstract: It is often held to be definitive of consciousness that there is something it is like to be in a conscious state. A consensus has arisen that 'is like' in relevant 'what it is like' locutions does not mean 'resembles'. This paper argues that the consensus is mistaken. It is argued that a recently proposed 'affective' analysis of these locutions fails, but that a purported rival of the resemblance analysis, the property account, is in fact compatible with it. Some of the implications of this argument are briefly explored: it is suggested that the meaning of 'what it's like' does not, in itself, have any special bearing on consciousness, and that the implications for the so-called 'hard problem' of consciousness are deflationary.